Pengaruh Penerapan Metode Ummi Terhadap Tartil Al-Qur’an Siswa SDIT Al-Ikhlas Samarang Garut - Fauziah, Hapsah; Febriyanti, Alicia (STAI Al-Musaddadiyah Garut, 2023)
Reading the Qur'an is not just about recitation; it must adhere to the rules of Tajwid (proper pronunciation and articulation), Makharijul Huruf (points of articulation of the letters), Shifatul Huruf (characteristics of the letters), and Tartil (slow and clear recitation). Students often struggle to read the Qur'an according to these guidelines, leading to many students reading without observing the correct rules. The Ummi method is one approach designed to assist students in reading the Qur'an correctly and proficiently. The objectives of applying the Ummi method in this study include: Describing the Tartil (correct and rhythmic recitation) of the Qur'an among students at SDIT Al-Ikhlas. Detailing the implementation of the Ummi method for students at SDIT Al-Ikhlas. Assessing the impact of the Ummi method on the Tartil of the Qur'an among students at SDIT Al-Ikhlas. This research employs a descriptive quantitative approach, collecting data to explore the phenomena under study. The findings regarding the impact of the Ummi method on the Tartil of Qur'anic recitation among students at SDIT Al-Ikhlas Samarang Garut are as follows: The analysis of the questionnaire for variable X (the Ummi method) yields an average score of 4.56, which falls into the high or very good category. For variable Y (Qur'anic recitation Tartil), the average score is 4.1. These results indicate that the Ummi method significantly influences Tartil of Qur'anic recitation among students at SDIT Al-Ikhlas Samarang Garut, with a substantial impact of 57.67%. The remaining 42.33% is influenced by other factors not covered in this study, aligning with the fundamental purpose and function of Qur'anic recitation. Keywords: Ummi Method, Tartil Al-Qur'an